Glycerol Trinitrate Acts Downstream of Calcitonin Gene-Related Peptide in Trigeminal Nociception—Evidence from Rodent Experiments with Anti-CGRP Antibody Fremanezumab - Benedicter, Nicola; Vogler, Birgit; Kuhn, Annette; Schramm, Jana; Mackenzie, Kimberly D.; Stratton, Jennifer; Dux, Mária; Meßlinger, Karl (Cells, 2024)
Calcitonin gene-related peptide (CGRP) and nitric oxide (NO) have been recognized as important mediators in migraine but their mechanisms of action and interaction have not been fully elucidated. Monoclonal anti-CGRP antibodies like fremanezumab are successful preventives of frequent migraine and can be used to study CGRP actions in preclinical experiments. Fremanezumab (30 mg/kg) or an isotype control monoclonal antibody was subcutaneously injected to Wistar rats of both sexes. One to several days later, glyceroltrinitrate (GTN, 5 mg/kg) mimicking nitric oxide (NO) was intraperitoneally injected, either once or for three consecutive days. The trigeminal ganglia were removed to determine the concentration of CGRP using an enzyme-linked immunosorbent assay (ELISA). In one series of experiments, the animals were trained to reach an attractive sugar solution, the access to which could be limited by mechanical or thermal barriers. Using a semi-automated registration system, the frequency of approaches to the source, the residence time at the source, and the consumed solution were registered. The results were compared with previous data of rats not treated with GTN. The CGRP concentration in the trigeminal ganglia was generally higher in male rats and tended to be increased in animals treated once with GTN, whereas the CGRP concentration decreased after repetitive GTN treatment. No significant difference in CGRP concentration was observed between animals having received fremanezumab or the control antibody. Animals treated with GTN generally spent less time at the source and consumed less sugar solution. Without barriers, there was no significant difference between animals having received fremanezumab or the control antibody. Under mechanical barrier conditions, all behavioral parameters tended to be reduced but animals that had received fremanezumab tended to be more active, partly compensating for the depressive effect of GTN. In conclusion, GTN treatment seems to increase the production of CGRP in the trigeminal ganglion independently of the antibodies applied, but repetitive GTN administration may deplete CGRP stores. GTN treatment generally tends to suppress the animals’ activity and increase facial sensitivity, which is partly compensated by fremanezumab through reduced CGRP signaling. If CGRP and NO signaling share the same pathway in sensitizing trigeminal afferents, GTN and NO may act downstream of CGRP to increase facial sensitivity.
CRIS-Team Scopus Importer:2024-04-26
Keywords: calcitonin gene-related peptide; CGRP concentration; CGRP release; fremanezumab; glycerol trinitrate; migraine pain; monoclonal antibody; rat

High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Mária; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2019)
Background: The α1-adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. Methods: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. Results: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. Conclusions: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. Significance: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
CRIS-Team Scopus Importer:2019-12-03

High-dose phenylephrine increases meningeal blood flow through TRPV1 receptor activation and release of calcitonin gene-related peptide - Dux, Maria; Babes, Alexandru; Manchen, Jessica; Sertel-Nakajima, Julika; Vogler, Birgit; Schramm, Jana; Meßlinger, Karl (European Journal of Pain, 2020)
BACKGROUND: The α1 -adrenoceptor agonist, phenylephrine, is used at high concentrations as a mydriatic agent and for the treatment of nasal congestion. Among its adverse side-effects transient burning sensations are reported indicating activation of the trigeminal nociceptive system. METHODS: Neuropeptide release, calcium imaging and meningeal blood flow recordings were applied in rodent models of meningeal nociception to clarify possible receptor mechanisms underlying these pain phenomena. RESULTS: Phenylephrine above 10 mM dose-dependently released calcitonin gene-related peptide (CGRP) from the dura mater and isolated trigeminal ganglia, whereas hyperosmotic mannitol at 90 mM was ineffective. The phenylephrine-evoked release was blocked by the transient receptor potential vanilloid 1 (TRPV1) antagonist BCTC and did not occur in trigeminal ganglia of TRPV1-deficient mice. Phenylephrine at 30 mM caused calcium transients in cultured trigeminal ganglion neurons responding to the TRPV1 agonist capsaicin and in HEK293T cells expressing human TRPV1. Local application of phenylephrine at micromolar concentrations to the exposed rat dura mater reduced meningeal blood flow, whereas concentrations above 10 mM caused increased meningeal blood flow. The flow increase was abolished by pre-application of the CGRP receptor antagonist CGRP8-37 or the TRPV1 antagonist BCTC. CONCLUSIONS: Phenylephrine at high millimolar concentrations activates TRPV1 receptor channels of perivascular afferents and, upon calcium inflow, releases CGRP, which increases meningeal blood flow. Activation of TRPV1 receptors may underlie trigeminal nociception leading to cranial pain such as local burning sensations or headaches caused by administration of high doses of phenylephrine. SIGNIFICANCE: Phenylephrine is used at high concentrations as a mydriaticum and for treating nasal congestion. As adverse side-effects burning sensations and headaches have been described. Phenylephrine at high concentrations causes calcium transients in trigeminal afferents, CGRP release and increased meningeal blood flow upon activation of TRPV1 receptor channels, which is likely underlying the reported pain phenomena.
EVALuna2:213473